An In Loco Theoretical and Practical Training Program for Nursing Professionals Regarding the Basic Maneuvers in Cardiopulmonary Resuscitation / Programa de Treinamento Teórico/Prático In Loco para Enfermagem Acerca das Manobras Básicas em Ressuscitação Cardiopulmonar - Ana Carolina Belmonte Assalin; Ledjane Neves Oliveira; Andressa Rodrigues Souza; Eliane Silva Grazziano; Regimar Carla Machado (Universidade Federal do Estado do Rio de Janeiro, 2019)
Objective: To evaluate an in loco theoretical and practical training program for nursing technicians and auxiliaries regarding the basic maneuvers in cardiopulmonary resuscitation. Methods: It's a quasi-experimental study that developed from August to October 2015. The participants were 96 nursing technicians and auxiliaries from a public hospital in the metropolitan region of São Paulo State. An instrument with twenty closed questions was applied before and immediately after the training. The results were analyzed by the Wilcoxon signed-rank test. Results: The nursing technicians and auxiliaries showed better performance in the post-test, respectively, 161% and 180%. The greatest performance was in the recognition of cardiorespiratory arrest (CRA), 83.3% for auxiliaries and 83.6% for technicians. One limitation of the study is that there has been no data regarding the professional practice before and after the training. Conclusion: The training proved to be effective since there was a significant increase in the correct post-test.